EFFECTS OF FACE MASKS ON CARDIORESPIRATORY PARAMETERS DURING EXERCISE VELOERGOMETRY TEST - Ozols, Edgars; Galeja, Zinta; Kaupužs, Aivars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The COVID-19 pandemic has sparked ongoing scientific discussions about the adverse effects of wearing face masks on cardiorespiratory indicators, and the subjective response to exertion. Many researchers have investigated the impact of wearing face masks on different physiological factors through various exercise routines, such as a progressive cycling test, the 6-minute walk test, and treadmill walking at a constant pace, yielding inconsistent findings. This study aimed to examine the physiological and perceptual responses of wearing surgical face masks during and after the veloegometry test. Fifteen healthy young adults (mean age, 26.8±4.4 years, 5 males and 10 females) conducted the Astrand-Rhyming veloegometry protocol twice (with and without masks). Physiological outcomes (heart rate, maximal oxygen uptake, and oxygen saturation level), perceived exertion, and discomfort feeling by modified Borg scale were assessed. No significant differences were observed in physiological outcomes with or without masks during increasing load intensities (p > 0.05) except for the last minute of testing and the minute after testing (p ≤ 0.005). Participants wearing masks reported the tendency of higher exertion level (3.8±1.08 vs 4.4±0.9) but statistical analysis can't definitively confirm it. While exercising with a face mask may not adversely affect cardiorespiratory factors, it can elevate perceived exertion levels and discomfort, particularly when exercise intensity exceeds a certain threshold.